Critical Discourse Analysis on the Politicians' Social Media Posts - Mandra Saragih; Arika Arika (English Teaching and Linguistics Journal (ETLiJ), 2020)
The research is dealt with critical discourse analysis on the politicians’ social media posts which is mainly aimed to Investigate the hoax phenomenon especially the content of politicians on the social media posts. The data of the research is taken from the politician status social media through downloading the the pictures, reading the content of pictures carefully, analyzing the hoax posts by using Lynda Walsh (2006), select and identify the hoax posts phenomenon of the politicians’ social media posts and to make the data be stronger, the researcher also did an interview with some people and it is acknowledged  that the hoax phenomenon of the politicians’ social media posts has brought the anxiety in the society life in approaching the presidential election 2019. It has many the power of context that made the society believed on it and to critical the case it is used the theory of  Van Djik’s framework 1988 and 2001 that focus critical discourse as language, ideology and power.The conclusion of this research is there were many various impacts and the influences toward the society who do not understand in choosing which is a hoax news or a fact news  on the social media because in all the pictures of the hoax posts that the researcher put on this thesis, it has proved based on interviewing some people and it has declared by communication and technology that the hoax posts phenomenon that has shared by the society and the politician is really problematic towards the irrational people.